Little women - Alcott, Louisa May (Usborne Publishing Ltd London, 2015)
This inspirational story follows the fortunes of the March sisters as they struggle through the American Civil War and learn the importance of love, family and following their dreams. Fully illustrated, this hardback edition is traditionally bound and has a ribbon page marker